On an Invariant Set in the Heat Conductivity Problem with Time Lag - M. Tukhtasinov; G. I. Ibragimov; N. O. Mamadaliev (Abstract and Applied Analysis)
The problems of weak and strong invariance of a constant multivalued mapping with respect to the heat conductivity equation with time lag are studied. Sufficient conditions of weak and strong invariance of a given multivalued mapping are obtained.